2022
DOI: 10.3390/su14084469
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Commuting Practices on Social Sustainability and Sustainable Mobility

Abstract: Commuting is an integral part of many people’s everyday life providing a transition between private and working life. It does, however, lead to negative impacts at a personal and social-ecological level (health impacts, lack of time, climate emissions, etc.). This article is based on the transdisciplinary research project “CommuterLab” (PendelLabor), which investigates commuting practices in the German Rhine-Main region. Using a practice-theoretical approach, we conducted a qualitative empirical study to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The practice-theoretical perspective is increasingly applied to the analysis of sustainability transitions and the transport transition, in particular [9,35,36]. In the context of the transport transition it has been applied to mobility practices of certain groups of society, e.g., elderly people [37] or commuters [15,38,39], to various transport modes, e.g., cycling [40] or car-sharing [41], as well as to the role of transport providers [36] and the development of transport scenarios [9].…”
Section: Analytical Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…The practice-theoretical perspective is increasingly applied to the analysis of sustainability transitions and the transport transition, in particular [9,35,36]. In the context of the transport transition it has been applied to mobility practices of certain groups of society, e.g., elderly people [37] or commuters [15,38,39], to various transport modes, e.g., cycling [40] or car-sharing [41], as well as to the role of transport providers [36] and the development of transport scenarios [9].…”
Section: Analytical Perspectivementioning
confidence: 99%
“…Local and regional transport planning practices cannot be changed easily, as they are embedded in a complex interplay with spatial, political, and financial conditions and the practices shaping those conditions. The practices described in this paper should not obscure the fact that prevailing conditions, such as the availability of parking spaces and commuter tax allowances, promote continued stability of car use [15]. Restructuring infrastructures that have been built over decades takes time [47].…”
Section: Drivers Of Changementioning
confidence: 99%
See 2 more Smart Citations
“…All these combined aid in enhancing both creativity and productivity. Several empirical studies have found that active commuters are found to be physically and mentally in a be er state, even if this is their only form of exercise [10,11].…”
Section: Introductionmentioning
confidence: 99%